The complex and heterogeneous evidence describing cell biology in neuroinflammation - Saavedra Torres, Jhan Sebastian; Guayambuco Medina , Maira Alejandra; Salazar, Margarita Rosa; Álvarez Camargo , Juan Carlos; Medina Ortega , Marco Antonio; Salguero , Carolina; Clavijo , Carlos Andrés (Interdisciplinary Journal of Epidemiology and Public Health, 2024)
Neuroinflammation is a complex integration of responses of all cells present within the Central Nervous System, including neurons, macroglia, microglia, and infiltrating leukocytes. Neuroinflammatory disorders occur when the immune system becomes too active and attacks healthy cells, having an underlying pathology surrounding them. The immune system can damage parts of the central nervous system. Cell biology is broad in addressing and defining a brain that faces inflammation. Understanding pro-inflammatory and anti-inflammatory action in the brain depends on microglia and astrocytes. Several animal studies have identified inflammatory markers, including IL-1, TNF-α, and IL-6 mRNA. A particular review by "Johns Hopkins Medicine International" concluded that understanding neuroinflammation from an ischemic lesion is paramount, proposing research perspectives and recognizing in vitro studies that allow us to search for alternative therapies to improve patients.